Activation of host transient receptor potential (TRP) channels by praziquantel stereoisomers. - Gihan S Gunaratne; Nawal A Yahya; Peter I Dosa; Jonathan S Marchant (Public Library of Science (PLoS), 2018)
The anthelmintic praziquantel (±PZQ) serves as a highly effective antischistosomal therapy. ±PZQ causes a rapid paralysis of adult schistosome worms and deleterious effects on the worm tegument. In addition to these activities against the parasite, ±PZQ also modulates host vascular tone in blood vessels where the adult worms reside. In resting mesenteric arteries ±PZQ causes a constriction of basal tone, an effect mediated by (R)-PZQ activation of endogenous serotoninergic G protein coupled receptors (GPCRs). Here, we demonstrate a novel vasodilatory action of ±PZQ in mesenteric vessels that are precontracted by high potassium-evoked depolarization, an effect previously reported to be associated with agonists of the transient receptor potential melastatin 8 channel (TRPM8). Pharmacological profiling a panel of 17 human TRPs demonstrated ±PZQ activity against a subset of human TRP channels. Several host TRP channels (hTRPA1, hTRPC3, hTRPC7) were activated by both (R)-PZQ and (S)-PZQ over a micromolar range whereas hTRPM8 showed stereoselective activation by (S)-PZQ. The relaxant effect of ±PZQ in mesenteric arteries was caused by (S)-PZQ, and mimicked by TRPM8 agonists. However, persistence of both (S)-PZQ and TRPM8 agonist evoked vessel relaxation in TRPM8 knockout tissue suggested that canonical TRPM8 does not mediate this (S)-PZQ effect. We conclude that (S)-PZQ is vasoactive over the micromolar range in mesenteric arteries although the molecular mediators of this effect remain to be identified. These data expand our knowledge of the polypharmacology and host vascular efficacy of this clinically important anthelmintic.